Importance of chlamydial antibodies in acute salpingitis in central Africa. Issue 3 (June 1987) - Frost, E; Collet, M; Reniers, J; Leclerc, A; Ivanoff, B; Meheus, A
Abstract : Of 35 women with acute salpingitis on laparoscopy, 86% had chlamydial antibodies at a titre of 1/16 or higher and 49% at a titre of 1/512 or higher. Geometric mean titres of chlamydial antibodies correlated significantly with a laparoscopic observation of chronic salpingitis (p less than 0.001), with a history of infertility (p less than 0.05), and with severe inflammation (p less than 0.10), but not with a history of salpingitis or a positive cervical culture for Chlamydia trachomatis. In the subgroup of infertile women, the geometric mean titre of antibodies to chlamydiae correlated significantly with the presence of chronic salpingitis (p less than 0.005). These data indicate that chlamydial infections play a major part in salpingitis and infertility in central Africa. In this area, which is known as the "infertility belt", programmes to control chlamydial infections should be implemented.